HUBUNGAN MOTIVASI DAN MINAT BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK KELAS V SDN NO 100311 PALSABOLAS PADA MATA PELAJARAN IPS T.A 2023/2024 - Khariani, Dwi Retno (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study aims to examine the relationship between motivation and learning interest with learning outcomes in Social Studies for fifth-grade students at SDN NO 100311 Palsabolas. Using a descriptive correlational method, this study collects data regarding motivation and interest, which are supporting factors for teaching and learning quality. Correlational techniques are used to determine the extent to which one variable is related to another. The results show a positive and significant relationship between learning motivation and learning outcomes. The correlation index between learning motivation and learning outcomes is 0.77, while the correlation index between learning interest and learning outcomes is 0.70. The t-value for learning motivation and learning outcomes is 5.95, and for learning interest and learning outcomes is 2.68, with an F-test value of 6.44. The coefficient of determination is 0.638, meaning that learning motivation and learning interest contribute 63.8% to the learning outcomes in Social Studies. Meanwhile, 36.2% is determined by other factors. Therefore, increasing motivation and learning interest is crucial in improving students' learning outcomes.